Perspectives from Systems-Level Key Informants on Optimizing Opioid Use Disorder Treatment for Adolescents and Young Adults - Jasper Yeh; Crosby Modrowski; Isabel Aguirre; Samantha Portis; Robert Miranda; Melissa Pielech (Children)
Background/Objectives: Rates of receiving opioid use disorder (OUD) treatment among adolescents and young adults (AYA) aged 16–25 are low. The current study qualitatively analyzed informants’ perspectives regarding the availability of, developmental considerations relevant to, and barriers associated with OUD treatment for AYA. Methods: Thirty key informants involved with OUD treatment in the northeastern United States completed individual, semi-structured interviews, including treatment providers (N = 11) and clinic leaders in programs that provide medication and psychosocial treatments for AYA with OUD (N = 10), as well as opioid-related policymakers (N = 6) and patient advocates (N = 3). Interviews were transcribed and independently double coded. Template-style thematic analysis methods were used and revealed seven themes. Results: The first theme highlighted limited treatment program availability for adolescents (aged < 18 years) with OUD. Four themes related to developmentally optimizing OUD treatment for AYA, describing the importance of caregiver involvement, AYA peer connections, wraparound services, and early intervention. Two themes described barriers to AYA OUD treatment, including stigma and knowledge gaps about medications for OUD as well as deficits in AYA’s access to basic resources (e.g., housing, food security) that prohibit effective participation in treatment. Conclusions: Results highlight concerns from systems-level key informants regarding gaps in OUD treatment options for youth under the age of 18 and a high need for OUD treatment that is developmentally tailored to AYA. Findings point toward potential modifications and additions to existing adult treatment programs to make OUD treatment more accessible, relevant, and engaging for AYA.